Factors Associated with the Quality of Pharmacy Service Provision in Denpasar, Bali - Made Novianita; I Nyoman Sutarsa; I Nyoman Adiputra (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: The approach of pharmacy service provision has shifted from rudimentary medicine distribution to becoming more patient centered. The objective of this study was to explore the factors that affect the quality of pharmaceutical care in pharmacist owned and managed (APA) pharmacies in Denpasar. Methods: Study was cross-sectional with 68 samples collected by systematic random sampling among 214 pharmacies at Denpasar City. Data was collected by interview with pharmacists, selfadministered- questionnaires to their staff and observation regarding the quality of services. Bivariate data analysis was conducted using chi square test and multivariate analysis was carried out using logistic regression. Results: Findings indicated that 48.5% (33 pharmacies) provide poor quality services. The presence of APA, the status of APA and the ownership of pharmacy affected the quality of pharmacy service. Multivariate analysis indicated that ownership of pharmacy was the most dominant variable impacting upon quality of pharmaceutical care (AOR=7.04; 95%CI: 1.5-33.8). Conclusion: The ownership of pharmacy affected the quality of pharmaceutical service provision in Denpasar.